Perspectives of 2D Materials for Optoelectronic Integration (Adv. Funct. Mater. 14/2022). (4th April 2022) - An, Junru; Zhao, Xingyu; Zhang, Yanan; Liu, Mingxiu; Yuan, Jian; Sun, Xiaojuan; Zhang, Zhiyu; Wang, Bin; Li, Shaojuan; Li, Dabing
Abstract : 2D Materials In article number 2110119, Bin Wang, Shaojuan Li, Dabing Li, and co‐workers discuss the state of the art of using 2D materials in optoelectronic integration. They also provide general advice for future development in this field.